Regionalism and the multilateral trading system : the role of regional trade agreements (OECD Pub. ParisFR, 2003)
Explores the relationship between the multilateral trading system and the regional trade agreements in 10 sectors that are increasingly covered in regional agreements. Concludes that regional trade agreements can complement, but cannot replace, coherent multilateral rules and progressive multilateral liberalisation
Bibliography: p. 8